Design and Implementation of Visible Light Communication based toys - Ain Najihah; Mohamed Hadi Habaebi; Farah Abdul Rahman (Institute of Advanced Engineering and Science, 2019)
This paper presents the design and implementation steps of a smart visible light communication based toy system equipped with laser sensors that can send and receive the data message based on the conversion of data from ASCII to binary code. The toy system intends to offer two-ways communication that will be a new medium for educational purposes for kids in their developmental stages in which both players can send and receive the data to and from each other toys equipped with sound indicator module to alert the player. Lastly, functionality and system testing were conducted to verify the functionalities of the system. A thorough implementation methodology details are presented in the paper.